It's the Opportunity Cost, stupid! How Self-Employment responds to Financial Incentives of Return, Risk and Skew - Peter Berkhout; Joop Hartog; Mirjam van Praag (Tinbergen Institute, 2011)
There is no robust empirical support for the effect of financial incentives on the decision to work in selfemploymentrather than as a wage earner. In the literature, this is seen as a puzzle. We offer a focus on theopportunity cost, i.e. the wages given up as an employee. Information on income from self-employment is ofinferior quality and this is not just a problem for the outside researcher, it is an imminent problem of theindividual considering self-employment. We also argue that it is not only the location of an incomedistribution that matters and that dispersion and (a)symmetry should not be ignored. We predict that highermean, lower variance and higher skew in the wage distribution in a particular employment segment reducethe inclination to prefer self-employment above employee status. Using a sample of 56,000 recent graduatesfrom a Dutch college or university, grouped in approximately 120 labor market segments, we find significantsupport for these propositions. The results survive various robustness checks on specifications andassumptions.
urn:nbn:nl:ui:29-432549
Keywords: J24; L26; 330; entrepreneurship; self-employment; wage-employment; income distribution; income risk; income skew; income variance; occupational choice; labor market entry; labor market segments; opportunity cost